The Influence of Brand Image and Service Quality on Customer Loyalty for Honda Motorcycles at Astra Motor Ahmad Yani Pontianak through Customer Satisfaction as an Intervening Variable - Nita Aulia Putri; Fita Kurniasari (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of brand image and service quality on customer loyalty for Honda motorcycles at Astra Motor Ahmad Yani Pontianak, with customer satisfaction as an intervening variable. This research uses an associative quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM–PLS) analysis technique using SmartPLS software. Data were collected from 100 respondents selected using purposive sampling. The results show that brand image and service quality have a positive and significant direct effect on customer satisfaction. The customer satisfaction variable also has a positive and significant effect on customer loyalty. Brand image is proven to have a direct effect on loyalty, while service quality does not have a direct effect on loyalty. The brand image and service quality variables have a positive and significant effect on customer loyalty through satisfaction as an intervening variable. The R² value shows that brand image and service quality can explain 51.4% of the variation in satisfaction, while brand image, service quality, and satisfaction together explain 72.3% of the variation in loyalty. The conclusion of this study emphasizes that a good brand image and consistent service play an important role in increasing satisfaction, which in turn strengthens customer loyalty. The practical implication is that Astra Motor Ahmad Yani needs to maintain a trustworthy brand reputation and continue to improve service quality evenly. Future research is suggested to examine other intervening variables such as trust or perceived value, as well as to expand the research object to different regions so that the results can be more generalizable.